Velocity changes around the Kaikōura earthquake ruptures from ambient noise cross-correlations. Issue 2 (22nd December 2021) - Madley, Megan; Yates, Alexander; Savage, Martha; Wang, Weiwei; Okada, Tomomi; Matsumoto, Satoshi; Iio, Yoshihisa; Jacobs, Katrina
SUMMARY: Seismic velocity changes before and after large-magnitude earthquakes carry information about damage present in the surrounding region. This study presents temporal velocity changes detected prior to and following the 2016 November M w 7.8 Kaikōura earthquake in Canterbury, New Zealand. We use continuous waveform data from 11 short-period seismometers within the Kaikōura region with an average interstation distance of 83 km. Nine-component day-long empirical Green's functions were computed for frequencies between 0.1 and 0.9 Hz for continuous seismic records from 2012 January 1 to 2018 February 28, which also include the 2013 Cook Strait and Lake Grassmere earthquakes. Using the moving-window cross-spectral method, seismic velocity changes were calculated. Immediately following the 2016 Kaikōura earthquake, a decrease in seismic velocity averaged across all component pairs of approximately 0.2 per cent was observed. An increase in seismic velocity of approximately 0.1 per cent after the earthquake was visible over a 1.5 yr period averaged across all component pairs. A depth sensitivity analysis suggests that observed velocity changes were confined to the uppermost 5 km of the subsurface. We consider strong ground motions a likely candidate for the seismic velocity decrease, followed by post-seismic relaxation via crack healing of the faults that ruptured in the Kaikōura region. Fault-zone damage may also have contributed to observed decreases in the vicinity of ruptured faults.